Perceptions, Uses, and Information Sources of Medical Cannabis Among Patients With Cancer - Vera Qu, BA; Caressa Hui, MD; Jennifer Hall, BA; Kekoa Taparra, MD, PhD; Tanaya Kollipara, BA; Sandy Trieu, MD; Beth Beadle, MD, PhD; Scott Soltys, MD; Erqi L. Pollom, MD (Advances in Radiation Oncology)
Purpose: Although medical cannabis (MC) has been shown to relieve cancer- and treatment-related symptoms, there is increasing misinformation regarding its antitumor efficacy. We aimed to identify opportunities for oncologists to communicate evidence-based guidance to patients regarding its use. Methods and Materials: Patients with cancer seen in radiation oncology clinic between June 2022 and July 2023 were surveyed with a questionnaire regarding their perceptions and information sources of MC. Associations between survey responses and demographic and disease variables were evaluated. Qualitative thematic analysis was performed on narrative responses in search of common themes. Results: Eighty-four patients (84% completion rate) were included in the analysis. Most (83.3%) strongly agreed or agreed that MC can provide symptom relief, whereas a subset of patients (15.5%) strongly agreed or agreed that MC can cure cancer. This latter subcohort was significantly more likely to identify as Hispanic/Latino (38.5% vs 9.9%, P = .009) and less likely to be up to date on COVID-19 vaccinations (30.8% vs 8.5%, P = 0.044). Identifying as Hispanic/Latino remained significantly associated with strongly agreeing or agreeing that MC can cure cancer on bivariate analysis (odds ratio, 6.528; 95% CI, 1.477-28.715; P = .012). Education level, other sociodemographic characteristics, and sources for information about MC were not significantly different between these patients. Thematic analysis revealed that patients hoped to learn more about MC from their oncologists but perceived them to be unknowledgeable on the subject. Conclusions: Although most patients consider MC to be a valuable addition to conventional therapies for managing refractory symptoms, a subset believed it had potential as an anticancer therapy. Many patients rely on unregulated sources, highlighting the need for providers to address misinformation, bridge knowledge gaps, and clarify its use.